Spike‐in SILAC proteomic approach reveals the vitronectin as an early molecular signature of liver fibrosis in hepatitis C infections with hepatic iron overload. Issue 9 (May 2014) - Montaldo, Claudia; Mattei, Simone; Baiocchini, Andrea; Rotiroti, Nicolina; Nonno, Franca Del; Pucillo, Leopoldo Paolo; Cozzolino, Angela Maria; Battistelli, Cecilia; Amicone, Laura; Ippolito, Giuseppe; van, Vera; Conigliaro, Alice; et al.
<x xml:space="preserve">Abstract</x> Hepatitis C virus (HCV)‐induced iron overload has been shown to promote liver fibrosis, steatosis, and hepatocellular carcinoma. The zonal‐restricted histological distribution of pathological iron deposits has hampered the attempt to perform large‐scale in vivo molecular investigations on the comorbidity between iron and HCV. Diagnostic and prognostic markers are not yet available to assess iron overload‐induced liver fibrogenesis and progression in HCV infections. Here, by means of Spike‐in SILAC proteomic approach, we first unveiled a specific membrane protein expression signature of HCV cell cultures in the presence of iron overload. Computational analysis of proteomic dataset highlighted the hepatocytic vitronectin expression as the most promising specific biomarker for iron‐associated fibrogenesis in HCV infections. Next, the robustness of our in vitro findings was challenged in human liver biopsies by immunohistochemistry and yielded two major results: (i) hepatocytic vitronectin expression is associated to liver fibrogenesis in HCV‐infected patients with iron overload; (ii) hepatic vitronectin expression was found to discriminate also the transition between mild to moderate fibrosis in HCV‐infected patients without iron overload.